2017
DOI: 10.1017/jfm.2017.491
|View full text |Cite
|
Sign up to set email alerts
|

Thrust generation from pitching foils with flexible trailing edge flaps

Abstract: In the present experimental study, we investigate thrust production from a pitching flexible foil in a uniform flow. The flexible foils studied comprise a rigid foil in the front (chord length $c_{R}$) that is pitched sinusoidally at a frequency $f$, with a flexible flap of length $c_{F}$ and flexural rigidity $EI$ attached to its trailing edge. We investigate thrust generation for a range of flexural rigidities ($EI$) and flap length to total chord ratio ($c_{F}/c$), with the mean thrust ($\overline{C_{T}}$) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Aside from their pertinence in the fish world, the experimental parameters (AR, Re and St) are similar to those selected in previous research about fluid-structure interactions of flapping foils (Lauder et al 2005;Godoy-Diana et al 2008;Dai et al 2012;Marais et al 2012;Dewey et al 2013;Quinn, Lauder & Smits 2014;Shinde & Arakeri 2014;Quinn, Lauder & Smits 2015;David et al 2017;Floryan et al 2017;Liu et al 2017;Rosic et al 2017;Zhu et al 2017). We explore a specific portion of the flow parameter space to understand how propulsive efficiency and surface distributions of hydrodynamic forces depend on shape and frequency at relatively low Reynolds numbers, a topic of high interest in the field of fin propulsion and for the practical design of underwater vehicles relying on bio-inspired undulating membranes.…”
Section: Morphologies and Kinematics Of The Fin Modelsmentioning
confidence: 80%
See 3 more Smart Citations
“…Aside from their pertinence in the fish world, the experimental parameters (AR, Re and St) are similar to those selected in previous research about fluid-structure interactions of flapping foils (Lauder et al 2005;Godoy-Diana et al 2008;Dai et al 2012;Marais et al 2012;Dewey et al 2013;Quinn, Lauder & Smits 2014;Shinde & Arakeri 2014;Quinn, Lauder & Smits 2015;David et al 2017;Floryan et al 2017;Liu et al 2017;Rosic et al 2017;Zhu et al 2017). We explore a specific portion of the flow parameter space to understand how propulsive efficiency and surface distributions of hydrodynamic forces depend on shape and frequency at relatively low Reynolds numbers, a topic of high interest in the field of fin propulsion and for the practical design of underwater vehicles relying on bio-inspired undulating membranes.…”
Section: Morphologies and Kinematics Of The Fin Modelsmentioning
confidence: 80%
“…As a measure of propulsive energy, we use η, the ratio between the energy employed to produce thrust and the sum of that energy with the energy employed to produce lateral forces (2.8). Figure 8 allows us to compare the efficiency thus defined for all foils with their respective flapping rates, as a function of St r and St. David et al (2017) have raised the question of whether or not the Strouhal number calculated from the tip excursion amplitude is a good metric for the width of a vortex wake. They showed that for highly flexible foils, the width of the wake is overestimated by the large tip excursion, and that a rigid projection of the pitching peduncle approximates better the vortices spacing.…”
Section: Spatio-temporal Distributions Of Fluid Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The desire to reproduce the elegant complexity of nature has inspired the fabrication of elaborate fins models [19][20][21][22][23][24]. Countless studies have resorted to particle imaging or particle tracking velocimetry (PIV and PTV) to investigate the flow topology and hydrodynamic forces of bio-inspired or authentic fish fins [25][26][27][28][29][30][31][32][33][34][35][36][37]. Euler-Bernoulli beam theory has also been employed to describe the fluid-structure interactions of fins and hydrofoils, addressing concepts such as foil compliance, damping effects, resonance frequency and efficiency optimization [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%